Peranan Kampung KB dalam pengendalian angka kelahiran di Kota Pangkalpinang Provinsi Bangka Belitung - Poli, Arnold; Pusung, Piet Hein; Pratiwi, Nayunda Rahmi; Giroth, Lady Grace Jane (Academy of Education Journal, 2024)
Indonesia's population growth has become a major concern due to its impact on various aspects of life. With the population reaching 275.77 million people in mid-2022, the growth rate decreased to 1.17 percent. This phenomenon is a serious concern for the government, especially with population density reaching 143.86 people/km2. Amidst efforts to address uncontrolled growth, Pangkalpinang City as an example shows a significant increase in population. To address this issue, the government introduced the Family Quality Village (Kampung KB) as a birth control program. Through Kampung KB, communities are educated about wise family planning and the importance of quality families. The program also provides support for couples who want to plan a family by providing information, counseling, and guidance related to various aspects of family planning. It is hoped that, through these efforts, the birth rate can be well controlled, which in turn will improve the quality of life of families and individuals and reduce the number of unplanned births.